An efficient way of increasing the total entropy of mixing in high-entropy-alloy compounds: a case of NaCl-type (Ag, In, Pb, Bi)Te1−xSex (x = 0.0, 0.25, 0.5) superconductors. Issue 26 (23rd June 2020) - Yamashita, Aichi; Jha, Rajveer; Goto, Yosuke; Matsuda, Tatsuma D.; Aoki, Yuji; Mizuguchi, Yoshikazu
Abstract : To investigate the multi-site alloying effect on the entropy of mixing (Δ S mix ) for the examined samples, the total Δ S mix for two crystallographic sites was calculated. Abstract : We propose an efficient way of increasing the entropy of mixing in high-entropy-alloy-type compounds, which can be achieved by multi-site alloying. As an example of this concept, we report the synthesis and observation of polycrystalline samples of new high-entropy-alloy-type metal chalcogenides (Ag, In, Pb, Bi)Te1− x Se x ( x = 0.0, 0.25, and 0.5) with a NaCl-type structure. The samples were synthesized using high pressure synthesis. Superconductivity with transition temperatures of 2.7, 2.5, and 2.0 K was observed with x = 0.0, 0.25, and 0.5, respectively. To investigate the multi-site alloying effect on the entropy of mixing (Δ S mix ) for the examined samples, we calculated the total Δ S mix for two crystallographic sites. For the samples with x = 0.25 and 0.5, Δ S mix reaches 1.89 R and 2.00 R, respectively, which exceed the Δ S mix of 1.79 R for a simple (single-site) high-entropy alloy containing six different elements.